Use of models for the environmental risk assessment of veterinary medicines in European aquaculture: current situation and future perspectives - Andreu Rico; Marco Vighi; Paul J. Van den Brink; Mechteld ter Horst; Ailbhe Macken; Adam Lillicrap; Lynne Falconer; Trevor C. Telfer (Wiley Publishing Asia Pty Ltd, 2025)
Veterinary Medicinal Products (VMPs) are used in intensive aquaculture production to treat a wide range of bacterial and parasitic infestations. Their release into the environment poses concerns regarding their potential ecotoxicological risks to aquatic ecosystems, which need to be evaluated making use of appropriate Environmental Risk Assessment (ERA) schemes and models. This study presents an overview of the major aquaculture production systems in Europe, the VMPs most commonly used, and the environmental quality standards and regulatory procedures available for their ERA. Furthermore, it describes the state-of-the-art on the development of environmental models capable of assessing the fate, exposure, ecotoxicological effects and risks of VMPs in aquaculture production systems, and discusses their level of development and implementation within European aquaculture. This study shows that the use of environmental models in regulatory ERA is somewhat limited in many European countries. Major efforts have been dedicated to assess the fate and exposure of antiparasitic compounds in salmonid cage systems, particularly in Scotland, while models and scenarios for assessing dispersal of antimicrobials, in general, and antiparasitic compounds in the Mediterranean as well as in Scandinavian regions are less available. On the other hand, the use of ecological models for assessing the effects and risks of VMPs is almost absent. Recommendations are provided to improve the chemical exposure and effect assessments and the ecological realism of the modelling outcomes, paying special attention to the protection goals set for the regulatory ERA of VMPs in Europe.